AB0626 Multicenter Registry in Inflammatory Myopathies: Preliminary Descriptive Study. (10th June 2014) - Nuño, L.; Lόpez Longo, F.J.; Llorente, I.; García De la Peña, P.; Cobo, T.; Almodόvar, R.; Lojo, L.; Díez, J.
Abstract : Background: Clinical manifestations, course and prognosis of idiopathic inflammatory myopathies (IIM) are extremely heterogeneous which, combined with its low prevalence, makes difficult the study of the disease in the absence of multicenter studies. Objectives: To analyze the clinical characteristics and mortality in a cohort of patients diagnosed with IIM in rheumatology units from several hospitals in Madrid. Methods: A multicenter retrospective longitudinal descriptive study of a cohort of patients diagnosed with IIM and in follow-up sometime between January 1980 and February 2013 in rheumatology from several hospitals in Madrid. All patients who met at least 2 criteria of Bohan and Peter 1 for polymyositis (3 criteria if dermatomyositis) were included. We performed a descriptive study ot the initial cases recruited during the first months of the stuydy. All patients in current follow-up signed informed consent. Statistical analysis was performed using SPSS 11.5 for Windows, with a significance level of p<0.05. Results: 127 cases were included in this study, with a 15% of patients lost to follow-up. There is a predominance of polymyositis over dermatomyositis (59.8% vs. 40.2% respectively). 74% of the cases were women, and patients had a medium age at diagnosis of 42.5±22.7 years, with a mean follow-up time of 76.8±70.8 months. Most of the cases were Caucasian (90.6% Caucasian, 7.9% Hispanic, 1.6% other). 97.6% met at least 3 criteria of Bohan and Peter. The most frequent form of classification were primary myopathies (47.6% primary myopathies, 26.2% myopathies associated with other connective tissue disease, 17.5% juvenile myopathies, 6.3% paraneoplastic myopathies, 1.6% inclusion body myopathies, and 0.8% necrotizing myopathies). Clinical manifestations associated with the disease included systemic manifestations (38.1%), joint manifestations (65.1%), skin manifestations (56.3%, the most frequent being Gottron sign) and interstitial lung disease (18.9%). EMG and muscle biopsy were performed in 96.1% and 66.9% and compatible with IIM in 92.6% and 77.6% of the cases respectively. 26 patients died (20.5%), mainly due to infections (26.9%), followed by cancer (19.2%), cardiovascular events (15.4%), interstitial lung disease (7.7%) and other causes. Conclusions: In this retrospective, longitudinal study on idiopathic inflammatory myopathies followed-up in several hospitals inMadrid, 127 have been recruited for the moment. The most common subtype were primary myopathies (47.6%). 20.5% of patientsdied, mainly due to infections, followed by cancer, cardiovascular events, interstitial lung disease and other causes. More cases willbe included. References: Bohan A, Peter JB. Polymyositis and dermatomyositis. N Engl J Med 1975 Feb 13;292(7):344-7. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3732